Prediction of highly stable 2D carbon allotropes based on azulenoid kekulene - Zhenzhe Zhang; Hanh D. M. Pham; Dmytro F. Perepichka; Rustam Z. Khaliullin (Nature Communications, 2024)
Abstract Despite enormous interest in two-dimensional (2D) carbon allotropes, discovering stable 2D carbon structures with practically useful electronic properties presents a significant challenge. Computational modeling in this work shows that fusing azulene-derived macrocycles – azulenoid kekulenes (AK) – into graphene leads to the most stable 2D carbon allotropes reported to date, excluding graphene. Density functional theory predicts that placing the AK units in appropriate relative positions in the graphene lattice opens the 0.54 eV electronic bandgap and leads to the appearance of the remarkable 0.80 eV secondary gap between conduction bands – a feature that is rare in 2D carbon allotropes but is known to enhance light absorption and emission in 3D semiconductors. Among porous AK structures, one material stands out as a stable narrow-multigap (0.36 and 0.56 eV) semiconductor with light charge carriers (m e  = 0.17 m 0,  m h  = 0.19 m 0), whereas its boron nitride analog is a wide-multigap (1.51 and 0.82 eV) semiconductor with light carriers (m e  = 0.39 m 0,  m h  = 0.32 m 0). The multigap engineering strategy proposed here can be applied to other carbon nanostructures creating novel 2D materials for electronic and optoelectronic applications.